Cavitation erosion resistant nickel-based cermet coatings for monel K-500. (July 2021) - Singh, Navneet K.; Ang, Andrew S.M.; Mahajan, Dhiraj K.; Singh, Harpreet
Abstract: WC-NiCr and WC-Hastelloy C coatings were deposited on Monel K-500 substrate by HVOF-spray with an aim to enhance cavitation erosion resistance of the alloy. The cavitation tests were performed for 10 h following ASTM G32-10 standard. Both WC-NiCr as well as WC-Hastelloy C coatings successfully reduced the erosion volume loss of the alloy by 59% and 9% respectively. The relatively superior performance of WC-NiCr coating could be attributed to better combination of its microhardness and fracture toughness. Formation of craters, cavities, and debonding of splats were found to be the signatures of cavitation erosion in the coatings. Whereas, microplastic tearing and microcracks were observed as the primary erosion mechanism in Monel K-500. Highlights: WC-NiCr and WC-Hastelloy C coatings were deposited on Monel K-500 by HVOF spray. Both the coatings enhanced the cavitation resistance of Monel. WC-NiCr coating recommended as a better choice for cavitation resistance. Hardness and fracture toughness jointly contribute to cavitation resistance. The coatings showed brittle fracture as the primary erosion mechanism.